Effect of an Epineurial-Like Biohybrid Nerve Conduit on Nerve Regeneration - Shu-Chih Hsieh; Chen-Jung Chang; Wen-Tung Cheng; Ting-Chen Tseng; Shan-Hui Hsu (Cell Transplantation, 2016)
A novel approach of making a biomimetic nerve conduit was established by seeding adipose-derived adult stem cells (ADSCs) on the external wall of porous poly(D, L-lactic acid) (PLA) nerve conduits. The PLA conduits were fabricated using gas foaming salt and solvent–nonsolvent phase conversion. We examined the effect of two different porous structures (GS and GL) on ADSC growth and proliferation. The GS conduits had better structural stability, permeability, and porosity, as well as better cell viability at 4, 7, and 10 days. The epineuriallike tissue was grown from ADSC-seeded conduits cultured for 7 days in vitro and then implanted into 10-mm rat sciatic nerve defects for evaluation. The regeneration capacity and functional recovery were evaluated by histological staining, electrophysiology, walking track, and functional gait analysis after 6 weeks of implantation. Experimental data indicated that the autograft and ADSC-seeded GS conduits had better functional recovery than the blank conduits and ADSC-seeded GL conduits. The area of regenerated nerve and number of myelinated axons quantified based on the histology also indicated that the autograft and AGS groups performed better than the other two groups. We suggested that ADSCs may interact with endogenous Schwann cells and release neurotrophic factors to promote peripheral nerve regeneration. The design of the conduit may be critical for producing a biohybrid nerve conduit and to provide an epineurial-like support.